2011
DOI: 10.1002/app.36263
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycidyl methacrylate‐grafted natural rubber on physical properties of polylactic acid and natural rubber blends

Abstract: Natural rubber (NR) was melt blended with polylactic acid (PLA) at various ratios using an internal mixer. The impact strength and elongation at break of PLA/NR blend dramatically increased with increasing NR content up to 10% (w/w). Glycidyl methacrylate‐grafted natural rubber (NR‐g‐GMA) was used as a compatibilizer for PLA/NR blend. The effects of content and %grafting of NR‐g‐GMA on mechanical properties of PLA/NR blend were studied. The experimental result showed that the addition of NR‐g‐GMA in PLA/NR ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
95
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 36 publications
10
95
1
Order By: Relevance
“…Ishida et al [4] observed two distinct phases in the PLA/rubber blends, many rubber particles were pulled out from the PLA matrix along with large voids being created during Izod impact testing. Similar result was also reported by Juntuek et al [27] for PLA/NR blends. Fig.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…Ishida et al [4] observed two distinct phases in the PLA/rubber blends, many rubber particles were pulled out from the PLA matrix along with large voids being created during Izod impact testing. Similar result was also reported by Juntuek et al [27] for PLA/NR blends. Fig.…”
Section: Mechanical Propertiessupporting
confidence: 92%
“…In order to improve compatibility and achieve a more advantageous combination of properties, several methods have been applied, e.g. the addition of block copolymers such as PCL-PLA diblock [33][34][35], triblock [33,36,37] and random copolymers, a PCL-PEG copolymer [38], a PEO-PPO-PEO triblock copolymer [39] or several commercial impact modifiers [40] compatibilizers [41][42][43]. The method possesses considerable potential, since structure and properties can be controlled relatively easily by the proper selection of components, blend composition and processing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is related to formulation of carbonyl groups in NR chains after hot shearing, which enhance the NR polarity resulting in higher compatibility between NR and PLA. Juntuek et al [141] proposed using of a glycidyl methacrylate grafted natural rubber (NR-g-GMA) as effective compatibilizer for PLA/NR blends. The effects of content and % grafting of NR-g-GMA on mechanical properties of PLA/NR blends were evaluated.…”
Section: Aliphatic Polyester/natural Rubber Blendsmentioning
confidence: 99%